Evaluating the impacts of new walking and cycling infrastructure on carbon dioxide emissions from motorized travel: a controlled longitudinal study - Brand, C; Goodman, A; Ogilvie, D (Elsevier, 2014)
Walking and cycling is widely assumed to substitute for at least some motorized travel and thereby reduce energy use and carbon dioxide (CO2) emissions. While the evidence suggests that a supportive built environment may be needed to promote walking and cycling, it is unclear whether and how interventions in the built environment that attract walkers and cyclists may reduce transport CO2 emissions. Our aim was therefore to evaluate the effects of providing new infrastructure for walking and cycling on CO2 emissions from motorised travel. A cohort of 1849 adults completed questionnaires at baseline (2010) and one-year follow-up (2011), before and after the construction of new high-quality routes provided as part of the Sustrans Connect2 programme in three UK municipalities. A second cohort of 1510 adults completed questionnaires at baseline and two-year follow-up (2012). The participants reported their past-week travel behaviour and car characteristics from which CO2 emissions by mode and purpose were derived using methods described previously. A set of exposure measures of proximity to and use of the new routes were derived. Overall transport CO2 emissions decreased slightly over the study period, consistent with a secular trend in the case study regions. As found previously the new infrastructure was well used at one- and two-year follow-up, and was associated with population-level increases in walking, cycling and physical activity at two-year follow-up. However, these effects did not translate into sizeable CO2 effects as neither living near the infrastructure nor using it predicted changes in CO2 emissions from motorised travel, either overall or disaggregated by journey purpose. This lack of a discernible effect on travel CO2 emissions are consistent with an interpretation that some of those living nearer the infrastructure may simply have changed where they walked or cycled, while others may have walked or cycled more but few, if any, may have substituted active for motorised modes of travel as a result of the interventions. While the findings to date cannot exclude the possibility of small effects of the new routes on CO2 emissions, a more comprehensive approach of a higher ‘dosage’ of active travel promotion linked with policies targeted at mode shift away from private motorized transport (such as urban car restraint and parking pricing, car sharing/pooling for travel to work, integrating bike sharing into public transport system) may be needed to achieve the substantial CO2 savings needed to meet climate change mitigation and energy security goals.